2019
DOI: 10.1016/j.carbon.2018.10.073
|View full text |Cite
|
Sign up to set email alerts
|

Perfect light absorption in graphene by two unpatterned dielectric layers and potential applications

Abstract: In the spectral range from ultraviolet to near infrared, graphene lacks the capability to support plasmon polaritons, and has low optical absorptivity for applications due to its extremely small thickness. Many photonic structures based on sophisticated nanofabrication or metal plasmonics have been adopted to conquer this limitation, but they suffer from high expenses or metal parasitic losses. Here, a single-channel coherent perfect absorber simply based on two unpatterned dielectric layers is proposed to rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 63 publications
(20 citation statements)
references
References 40 publications
0
17
0
Order By: Relevance
“…Our theoretical study has shown that almost perfect absorption (>99%) can be obtained over a wavelength range of ~300 nm with a choice of naturally available materials for the prism and the cavity layer, which is the best as far as we know. The proposed absorption scheme based on the wavelength-insensitive phase matching will be also useful for applications such as optical sensors 2325 , solar cells 26 , thermal emitters 27 , and nonlinear optics 28 .…”
Section: Introductionmentioning
confidence: 99%
“…Our theoretical study has shown that almost perfect absorption (>99%) can be obtained over a wavelength range of ~300 nm with a choice of naturally available materials for the prism and the cavity layer, which is the best as far as we know. The proposed absorption scheme based on the wavelength-insensitive phase matching will be also useful for applications such as optical sensors 2325 , solar cells 26 , thermal emitters 27 , and nonlinear optics 28 .…”
Section: Introductionmentioning
confidence: 99%
“…In view of this, the incident wave is intended to have the electric field sufficiently located within the ultrathin layer at any incident angle. Based on our previous work, an incidence of TE wave is better to make the light-matter interaction as strong as possible [26][27][28]. Therefore, we mainly focus on the use of TE wave for the detection.…”
Section: Design and Methodsmentioning
confidence: 99%
“…Compared to plasmons in traditional noble metals, graphene is two-dimensional (2D) nanomaterials that have been demonstrated to support localized surface plasmons with considerable field confinement in the infrared region, which offer a new class of platform to realize novel electronic and photonic devices in ultracompact sizes [ 11 , 12 , 13 ]. With the advantages of low propagation loss and actively tunable resonance wavelength in the infrared region, graphene plasmons (GPs) exhibit unique features that are not available in traditional metallic surface plasmons and have been widely used in infrared spectroscopy [ 14 , 15 , 16 , 17 , 18 , 19 , 20 ]. Recently, it was demonstrated that graphene plasmons can be tuned and enhanced by double or multi-layer graphene nanostructures [ 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%